Fund and non - member States : some legal effects - Gold, Joseph (Washington, 1966)
The relationship of an international organization to non-members raises a number of issues, not only in connection with the growing law of international organizations but also in connection with the older law of treaties. One of the leading issues is the legal effect of a treaty on states that are not parties to it ("third" states, "strangers"). Writing in 1960 as the Special Rapporteur of the International Law Commission, Sir Gerald Fitzmaurice, now Judge Fitzmaurice of the International Court of noted that the literature on this "amorphous and rather protean topic" was sparse and that both theory and doctrine were unsatisfactory.
Keywords: Financial economics